Social determinants, health disparities and linkages to health and health care - Kronenfeld, Jennie J. (Research in the sociology of health care ;, 2013)
This volume looks at the key links between social determinants, health disparities and health and health care. There is a particular focus on macro-level systems and micro-level issues, including the examination of issues for patients, carers and providers of care. Coverage includes papers on geographical and place factors and disparities, SES and race/ethnicity factors, chronic care and serious health problems such as HIV/AIDs and kidney transplantation, comparative aspects and perceptions of health disparities. Starting with an introduction that reviews the crucial sociological literature on social determinants and health disparities, papers in this volume go on to cover key themes including ageing, barriers to care, ethnicity, social inequalities, the views of parents on their childrens care, and doctor/patient relationships.